Implementasi Proses Asuhan Gizi Terstandar Pada Remaja Dengan Gagal Ginjal Kronik Stadium V, Nefritis Lupus dan Hipertensi di Ruang Gardenia 1 RSUP Prof. DR. I.G.N.G. Ngoerah - Sariasih, Ni Nyoman; Hariani, Gusti Ayu Nyoman; Hasikin, Hijrah; -, Nursalim (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Chronic Kidney Diseases is a global health problem with increasing prevalence, high morbidity, and frequent comorbidities such as malnutrition and hypertension. This case study presents a nutritional care process for a pediatric patient diagnosed with CKD Stage V undergoing regular hemodialysis, lupus nephritis, controlled Stage II hypertension, and mild protein-energy malnutrition. The study was conducted in Gardenia 1 Ward of Prof. Dr. I.G.N.G. Ngoerah General Hospital using an observational and descriptive approach through the Nutrition Care Process (NCP), including screening, comprehensive assessment (anthropometric, biochemical, clinical, and dietary history), diagnosis, intervention, monitoring, and evaluation. The patient was found to be at high risk of malnutrition with inadequate oral intake, disease-related malnutrition, abnormal biochemical markers, and suboptimal dietary habits. Nutritional intervention was provided in the form of a kidney diet, with energy administered gradually: starting at 60% (1281 kcal/day) for the first three days and increasing to 80% (1708 kcal/day) over the next three days. Protein intake (15% of total energy, 80.06 g/day) was also increased gradually from 60% (48.1 g/day) to 80% (64 g/day). Fat comprised 25% of total energy (59.3 g/day), provided in stages from 60% (35.6 g/day) to 80% (47.4 g/day). Carbohydrate intake accounted for 60% of energy (320.3 g/day), gradually increased from 60% (192.2 g/day) to 80% (256.2 g/day). The conclusion showed that patients were at high risk of malnutrition based on the results of nutrition screening using Strong Kids. Through the standardized nutritional care process carried out, there was an increase in food intake during the 6 days of intervention even though it had not reached 100% of the total requirement (RDA). This is influenced by the physical and clinical condition where at the beginning of the intervention there were still complaints of tightness and chest pain, but by the end of the intervention the complaints had disappeared. The results of the laboratory examination showed that the patient's Hb level was still below normal, which was 8.2 g/dL. This is not only influenced by iron (Fe) deficiency but also affected by the pathophysis of chronic kidney diseases, where the deteriorating condition of the kidneys causes disruption of the process of red blood cell formation (erythropoiesis) and shortening the life of erythrocytes due to uremia. Re-education in nutrition significantly improved the patient and family’s understanding and adherence to dietary recommendations. Continued monitoring and outpatient follow-up are essential to support nutritional recovery and clinical stability. The gradual provision of nutritional interventions and continuous education not only helps meet the nutritional needs of the patient but also strengthens the role of the family in supporting the child's dietary adherence. This case study highlights the importance of integrated services between medical care and nutritional intervention in efforts to holistically improve the quality of life of pediatric CKD (Chronic Kidney Disease) patients.